Babassu coal as a thermal source for absorption refrigeration system in the state of Maranhão - Nascimento, Ubiraci Silva; Nascimento, Sandra Maria Cruz; da Silva Neto, André Santos; Pestana Filho, José de Ribamar; Beckman, Valter Valder Reis (Seven Editora, 2023)
In this work a theoretical analysis of the integral use of babassu as an energy source was developed, seeking to emphasize the potential added to coal. A case study was carried out in the municipalities of Maranhão, aiming to diagnose aspects that relate the man of the field to this important source of biomass. The cooling system consists of a coupling of an oven driven with babassu charcoal in a Platen-Munters absorption refrigerator, through a closed two-phase thermosyphon. The results obtained resulted from a comparative analysis of an experiment already carried out with a similar system, powered by a wood stove, where it was perceived as a significant improvement in the efficiency of the proposed system. The babassu charcoal with the calorific value of the order of 7,300 kcal/kg, allowed us to obtain the amount of coal mass (load) to be used to feed every 10 min the oven to keep running the refrigerator of power of the order of 260w. As an optimization of the process, we propose a load of 400g with a supplied interval of 4hs to keep the refrigerator running.DOI:https://doi.org/10.56238/alookdevelopv1-102